Genotypic characterization of five subspecies of Mycobacterium kansasii. - Picardeau, M (1997)
Different molecular typing methods including restriction fragment length polymorphism (RFLP) analysis with the major polymorphic tandem repeat (MPTR) probe and the IS1652 probe, pulsed-field gel electrophoresis (PFGE), amplified fragment length polymorphism (AFLP) analysis, and PCR restriction analysis of the hsp-65 gene (PRA) were applied to clinical and water isolates of Mycobacterium kansasii. RFLP with the MPTR probe, PRA, PFGE, and AFLP analysis revealed five homogeneous clusters which appeared to be subspecies. RFLP with the MPTR probe and PRA gave patterns specific for each cluster, whereas PFGE and AFLP analysis gave polymorphic patterns. IS1652 was present in two of the five clusters and provided polymorphic patterns for one cluster only. The two IS1652-positive clusters were Accuprobe negative (Accuprobe test; Gen-Probe Inc.), and only two other clusters were Accuprobe positive. A PCR test based on the detection of a species-specific fragment (M. Yang, B.C. Ross, and B. Dwyer, J. Clin. Microbiol. 31:2769-2772, 1993) was positive for all M. kansasii strains. This PCR test is an accurate, rapid, and specific M. kansasii identification test. No subspecies was particularly more virulent, because all clusters contained clinical strains, from AIDS patients and non-AIDS patients, and environmental strains.